Design of wide band slotted microstrip patch antenna with defective ground structure for ku band - Akhila John Davuluri; P. Siddaiah (Institute of Advanced Engineering and Science, 2021)
This paper proposes a microstrip patch antenna (MSPA) in the Ku band for satellite applications. The antenna is small in size with dimensions of about 40 mm×48 mm×1.59 mm and is fed with a coaxial cable of 50 Ω impedance. The proposed antenna has a wide bandwidth of 3.03 GHz ranging from 12.8 GHz to 15.8 GHz. To realize the characteristics of wideband the techniques of defective ground structure (DGS) and etching slots on the radiating element are adopted. The antenna is modeled on the FR4 substrate. A basic circular patch is selected for the design of a dual-frequency operation and in the next step DGS is introduced into the basic antenna and enhanced bandwidth is achieved at both the frequencies. To attain wider bandwidth two slots are etched on the radiating element of which one is a square ring slot and the second one is a circular ring slot. The novelty of the proposed antenna is a miniaturized design and unique response within the Ku band region which is applicable for wireless UWB applications with VSWR